2020
DOI: 10.13057/biodiv/d211021
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and honey properties of stingless bees from meliponiculture in East and North Kalimantan, Indonesia

Abstract: Abstract. Syafrizal, Ramadhan R, Kusuma IW, Egra S, Shimizu K, Kanzaki M, Arung ET. 2020. Diversity and honey properties of stingless bees from meliponiculture in East and North Kalimantan, Indonesia. Biodiversitas 21: 4623-4630. Kalimantan Island in Indonesia is covered by tropical rain forests that are rich in biodiversity. Species, include a stingless bee (Trigona spp.). Recently, stingless bee beekeeping (Meliponiculture) in this region has become popular because the honey has a unique taste, a mix of swee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
0
28
0
4
Order By: Relevance
“…A phytochemical test was used to screen for the presence of flavonoids, alkaloids, terpenoids, tannins, steroids, saponins, phenolics, carotenoids, coumarin and carbohydrates. Screening tests for these major phytochemicals were carried out using standard qualitative procedures, as described in Syafrizal et al (2020), as follows:…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…A phytochemical test was used to screen for the presence of flavonoids, alkaloids, terpenoids, tannins, steroids, saponins, phenolics, carotenoids, coumarin and carbohydrates. Screening tests for these major phytochemicals were carried out using standard qualitative procedures, as described in Syafrizal et al (2020), as follows:…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…Panjang tubuh lebah tanpa sengat tersebut dapat menjadi salah satu cara sederhana dalam memilih spesies yang akan dibudidayakan (meliponikultur). Ukuran panjang tubuh lebah tanpa sengat yang besar dapat meningkatkan jumlah produksi madu yang dihasilkan, seperti H. itama yang menghasilkan jumlah produksi madu, propolis, dan polen lebih banyak daripada T. laeviceps (Priawandiputra et al 2020;Syafrizal et al 2020). Perlu penelitian lebih lanjut mengenai hubungan antara karakter morfologi dan morfometrik terhadap parameter meliponikultur.…”
Section: Pembahasanunclassified
“…The antioxidant activity values of IC50 and the original concentration of H. itama honey was 43.54 ppm (Karya Merdeka), 59.91 ppm (Tanah Merah), <25 ppm (Penajam), 61.35 ppm (Buana Jaya) and 71.27 ppm (Saing Prupuk). Syafrizal et al (2020) stated that H. itama from Tanah Merah has flavonoid, coumarin, saponin, tannins, alkaloids and carbohydrates compounds and the origin of Tarakan is only saponin compounds that are not present in the honey.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Likewise, Chua et al (2013) that phenolic and flavonoids found in honey are compounds that play an essential role as antioxidants. Tuksithaa et al (2018) reported that H. itama honey collected from Serawak has 47.40% inhibition, a high category. Shamsudin et al (2019a) suggested that H. itama's antioxidant activity was good for human health.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation